j-QAF programme: an effort towards strengthening the Islamic education in Malaysia - Suhid, Asmawati; Che Noh, Mohd Aderi; Abdul Mutalib, Lukman (IDOSI Publications, 2014)
The implementation of j-QAF programme in thenational schools in Malaysia has already completed its first round. The j-QAF model was introduced by the Ministry of Education Malaysia throughthe Islamic and Moral Education Department beginning 2005. It was another effort by the governement to encourage and improve further the teaching of Islamic Education in schools In the j-QAF programme, students are given exposure to the Jawi Remedial Class Model, the 6-month Model of Khatam Qur’an, the Arabic Language Communication Model and the Smart Prayers Camp Model. The j-QAF teachers were required to use these models as a basic guideline in the teaching and learning process. During the implementation of the j-QAF programme and the usage of the j-QAF models, they will definitely be aware of their strengths and weaknessess. Hence, this article will report and discuss the overall findings of the study on the implementation of the j-QAF program and models. A total of 309 j-QAF teachers in Selangor, Malaysia were involved as the research sample. Data collected were analyzed using the Statistical Package for The Social Science (SPSS)programme. The researcher gives suggestions and proposals to overcome the weaknesses and problems faced during the implementation of the j-QAF programme.